The Factors Affecting Aesthetic Education Development of Chinese Higher Education Institutions - Aliu , Rongyu; Lertlit , Supinda (Journal of Roi Kaensarn Academi, 2023)
This research aimed to identify and analyze the factors influencing the development of aesthetic education at S University, a higher education institution in Yunnan Province, China. A mixed-methods approach was employed, using both qualitative and quantitative research techniques. A sample of 400 students was selected using a probability sampling method from a total population of 4,500 students engaged in aesthetic education. Semi-structured interviews were conducted with six teachers and six students, providing in-depth insights into their roles in aesthetic education. Further, quantitative analyses were undertaken using beta values to determine the strength and significance of the relationships between independent variables (aesthetic literacy, aesthetic courses, aesthetic activities, and aesthetic experience) and the development of aesthetic education. The findings suggested that aesthetic classes significantly impacted aesthetic education development, followed by aesthetic literacy and aesthetic activities. Conversely, aesthetic experience was found to have an insignificant influence. This study provides crucial insights for policymakers, educators, and administrators seeking to improve the effectiveness of aesthetic education programs in higher education institutions.